Development of a Problem-Based Learning E-Books to Enhance Students’ Creative Thinking Skills in Senior High School - Aiyesi, Salwa; Jumadi, Jumadi; Prasetyo, Zuhdan Kun (Jurnal Pendidikan Fisika, 2025)
The development of students' creative thinking in physics remains a challenge due to the dominance of conventional instructional methods that lack interactive and contextual engagement. This study addresses the urgent need for innovative digital learning resources by developing an interactive physics e-book based on the Problem-Based Learning (PBL) model, focusing on optical device topics. The objective is to enhance students’ creative thinking skills through student-centered learning integrated with digital platforms. Using the ADDIE development framework (Analysis, Design, Development, Implementation, Evaluation), the e-book was designed and validated for its design, content, construct, and creative thinking assessment tools. Validation results showed high Aiken’s V scores across all components, indicating strong validity. Effectiveness was tested through a quasi-experimental approach involving 35 senior high school students, using pretest and posttest instruments. The N-Gain scores for both modeling (0.702) and implementation classes (0.707) demonstrated significant improvements in students’ creative thinking, categorized as high. The novelty of this study lies in the integration of Heyzine and Liveworksheet platforms with PhET virtual labs, providing an interactive, accessible, and collaborative learning environment. The findings suggest that the developed PBL-based e-book effectively facilitates contextual learning and fosters creative problem-solving skills. In conclusion, this e-book serves as a validated and impactful instructional tool that contributes meaningfully to physics education by promoting higher-order thinking through innovative digital pedagogy.